Soil Bio-Impact Effectiveness for the Optimal Multicriterial Environmental Sustainability in Crop Production - Vilma Naujokienė; Daiva Rimkuvienė; Egidijus Šarauskis (Agronomy, 2020)
Different bio-impacts affect the various properties and composition of soil, plant residues, harvests, and technological processes, as well as the interactions between different parts of the soil, working machine tools, energy consumption and environmental pollution with harmful gases. To summarize the wide-coverage investigations of various aspects of different bio-impact parameters, a multicriteria evaluation was conducted. Experimental research shows that different bioeffects such as those of agricultural practices can be oriented towards a reduction in fuel consumption, followed by reductions in CO2 emissions from machinery and changes in soil properties, dynamics of composition, yield and other parameters. A multicriteria assessment of the essential parameters would give farmers new opportunities to choose one optimal decision for reducing fuel consumption and increasing agricultural production, thereby reducing the negative environmental impact of soil cultivation processes, increasing yields and improving soil. Of all the properties investigated, from a practical point of view, the selection of the most important of all the essential links, such as reducing energy and expenditure, reducing environmental pollution, improving soil, and increasing yields and productivity, is reasonable. The evaluation of the bio-impact effects in agriculture by accounting for many criteria from several aspects was the main objective of the multicriteria assessment using the analytic hierarchy process. Based on the results of a multivariable research of fuel consumption—C1, C2, yield—C3, CO2 from soil—C4, density—C5, total porosity—C6, humus—C7, soil stability—C8, and soil moisture content—C9, the evaluation used experimental research data and the Simple Additive Weighting (SAW) mathematical method to find the best-case scenario. Multicriteria effectiveness was most pronounced after the first and third soil bio-impacts by using a solution of essential oils of plants, 40 species of various herbs extracts, marine algae extracts, mineral oils, Azospirillum sp. (N), Frateuria aurentia (K), Bacillus megaterium (P), seaweed extract. The most important goal was to achieve the best soil bio-impact effectiveness—minimized energy consumption from ploughing and disc harrowing operations, parallelly minimized harmful emissions from agricultural machinery, minimized CO2 from soil, soil density, maximized soil total porosity, soil humus, soil stability, yield and optimized soil moisture.